2020
DOI: 10.1002/fes3.239
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteome and transcriptome analyses revealed key factors involved in tomato (Solanum lycopersicum) under high temperature stress

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 62 publications
1
22
1
Order By: Relevance
“…Thus, the transcriptome and proteome data used in the present analyses were obtained from different sets of patients. Although, the number of co‐differentially expressed genes/proteins identified in the present study were higher as compared to those reported in previous studies ( 51 53 ). We select the DEPs based on P and Log2FC values ( 27 , 28 ).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Thus, the transcriptome and proteome data used in the present analyses were obtained from different sets of patients. Although, the number of co‐differentially expressed genes/proteins identified in the present study were higher as compared to those reported in previous studies ( 51 53 ). We select the DEPs based on P and Log2FC values ( 27 , 28 ).…”
Section: Discussioncontrasting
confidence: 87%
“…Since the present study utilized publicly available transcriptomics databases and proteomics results from the current assessment, this 122 co-differentially expressed genes/proteins might be considered as representative of altered biological processes. In previous studies using transcriptomics and proteomics data, obtained from the same sample for both techniques, reported co‐differential expression of genes/proteins in the range of 31–149 ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other genes maintained upregulation patterns for protein processing in ER and ubiquitination ( Derlin , Sec 61 , OS9 , Ubx , p97 , Ufd1 , UbcH5 , HRD1 , SAR1 ) in V. darrowii at 6-h stress, and a few specific genes showed upregulation ( Ubx , Ufd1 , and Sec23/24 , cull ) and downregulation ( eLF2 ) patterns at 9-h stress. Previous studies reported DEGs involved in protein processing in ER such as protein homeostasis (sHSF), luminal chaperon ( NEF, GRP94 ), chaperon binding protein (BiP), protein folding machinery ( CRT , CNX , PDIs , UGGT , HSPs), protein translocation ( Sec 61, 23/24), and ubiquitination ( Derlin , OS9 , Ubx , p97, Ufd1 , UbcH5 , HRD1 , SAR1 ) and other mechanisms involved in the heat stress response in plants [ 33 , 34 , 35 , 36 , 37 ]. The differential expression patterns of protein processing genes in ER suggest a prevalence in differential response and possible protein homeostasis and repair mechanisms under heat stress in blueberry species.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of biologically meaningful patterns using data integration is now emerging as one of the most evolving fields in modern data science but there are very few such studies for plants ( Ding et al, 2020 ; Zhang et al, 2020 ). This work began with an aim to identify and investigate the plant prionome in order to explore a general role in memory based on the previous but limited reports of PrLPs having a role in flowering and plant memory.…”
Section: Discussionmentioning
confidence: 99%